Disain UX Aplikasi Merdeka Belajar – Kampus Merdeka menggunakan Disain Sprint Google - Akbar, Rufman Iman; Siregar, Johannes Hamonangan; Anwar, Chaerul (STMIK PONTIANAK, 2024)
Students must have a solid understanding of the Independent Learning-Independent Campus Policy, which was introduced by the Ministry of Education, Culture, Research, and Technology in 2020. Students are unwilling to participate in programmes due to a lack of knowledge and false information about it, so an information system is needed to prepare and handle these programmes. The goal of this study is to create an UX design for information system that will enable students in understanding programme policies and participating in programme activities. The technique of this study focuses on creating UX design that satisfy the policy's requirements while taking into account the needs of students. Students from Universitas Pembangunan Jaya's Department of Information Systems make up the data population. Google Sprint Design is the UX design methodology employed in this study. The six phases of the Google Sprint design process are Understand, Define, Sketch, Decide, Prototype, and Validate. The application development team uses the UX design outcomes after they have been demonstrated to be effective. It has been demonstrated in this study that design outcomes can take system stakeholders' needs into account.